2022
DOI: 10.1097/md.0000000000029350
|View full text |Cite
|
Sign up to set email alerts
|

Intraspinal choristoma in the lumbar region: A case report

Abstract: Rationale: Intraspinal choristoma is a relatively uncommon intervertebral canal tumor. Prior to our reports, only 2 cases of intraspinal choristoma had been reported. Because this disease is not common and looks like a mass of fatty tissue on the magnetic resonance imaging (MRI), intraspinal choristoma can be easily misdiagnosed as teratomas or lipomas (like the case of this article presenting) without a pathology report. So if a lumber intraspinal lesion is discovered in a clinical examination, int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Throughout the pathological examination, the tumor was found to comprise both striated muscle and glandular tissue. Yang et al [ 6 ] reported a case of intraspinal choristoma combined with spinal cord tethering syndrome in the lumbar region. In this report, we described a case of intradural extramedullary spinal choristoma at the lumbar segment, which was composed of fibrous adipose tissue and blood vessels and covered with flattened epithelium.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Throughout the pathological examination, the tumor was found to comprise both striated muscle and glandular tissue. Yang et al [ 6 ] reported a case of intraspinal choristoma combined with spinal cord tethering syndrome in the lumbar region. In this report, we described a case of intradural extramedullary spinal choristoma at the lumbar segment, which was composed of fibrous adipose tissue and blood vessels and covered with flattened epithelium.…”
Section: Discussionmentioning
confidence: 99%
“…To date, only 4 cases of spinal choristoma have been recorded. [3–6] This report presents a unique case of a choristoma situated in the lumbar spinal canal. The clinical manifestations, imaging findings, and pathological alterations of this unusual case are discussed in detail, providing novel insights distinct from those of previously reported cases.…”
Section: Introductionmentioning
confidence: 99%